Developing translation-oriented research competence: what can we learn from professional translators?. Issue 3 (3rd July 2019) - Gough, Joanna
ABSTRACT: The technologisation and industrialisation of the translation process have had an impact on translation practice and, consequently, on the way translators carry out their translation-related research. This necessitates a response from the research communities to examine this impact and the ensuing changes in translation practice, with the way translator trainers approach training and the development of relevant competences being one of the biggest considerations. This paper reports on a study of the research activities of 16 freelance professional translators during a translation task in their natural working environment. The findings are relevant to translator trainers in terms of competences associated with information acquisition and utilisation during the translation process to inform the development of these competences. More specifically, a spectrum of the translator resource behaviour as well as patterns of research distribution are identified, highlighting their relevance for the changing nature of the translation process in new technological environments. New areas of interest for translator trainers are suggested, including diversification of student practice with regard to search strategies and the use of external resources, distribution of research phases, as well as raising awareness of how technological innovations may impact translation-oriented research activities.